Safety integrity level evaluation of nuclear centrifugal pump based on performance degradation data. (April 2018) - Lin, Zhao; Xue, Wang
To reduce personnel and equipment risks related to centrifugal pumps in nuclear power plants, safety integrity level for centrifugal pumps must be evaluated. The safety integrity level evaluation methods in the IEC 61508 standard depend on statistical historical failure-dependent data and static threshold. However, for centrifugal pumps in nuclear power plants, the statistical historical failure-dependent data are insufficient, and the static threshold is not easily determined, especially under dynamically changing operation conditions. To overcome the aforementioned problems, this article proposes a safety integrity level evaluation method for centrifugal pumps based on the performance degradation data. This method constructs a Wiener degradation model to describe the degradation process of centrifugal pumps. The degradation trajectories in the upcoming cycles are predicted using a particle filter algorithm. The degradation trajectories with high credibility are selected based on reputation index. The failure time of each selected degradation trajectory is judged using catastrophe theory. The safety integrity levels are defined by performance degradation threshold on demand. Experiments are performed using the simulation data and the component cooling water pump condition-monitoring data set. By comparing to the risk matrix analysis recommended in the IEC 61508 standard, the proposed method is more reasonable and obeys the rule of the bathtub-shaped curve.